Buddhist Principles of Self-Management: Integrating Morality, Mindfulness, and Wisdom into Modern Leadership and Organizational Practice - Singh , Monu; Nanga, Roopalatha; Jaffer, Syed (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
This paper offers a redefined, self-management through the lens of ethics, drawing on the early Buddhist canonical texts. By employing a qualitative thematic methodology from focused studies of the, Dīgha Nikāya; Majjhima Nikāya; and, Aṅguttara Nikāya, this study seeks to define self-management as a cohesive, systemic construct that consists of ethical discipline (sīla), mental discipline (samādhi), and wisdom (paññā), and is undergirded by mindfulness (sati) and non-attachment (virāga). The findings reveal that self-management as ethical self-governance is early Buddhism’s perspective as opposed to the understanding of self-management as a neutral and psychological phenomenon. Sila establishes, the self-restraint, moral accountability and trust in the social system; samādhi helps to stabilize attention along with the regulation of emotional reactivity; and, paññā assists in turbulent times with respect to the, reflection under conditions of, complexity and ambiguity. Sati serves as ethical vigilance; allowing persons to unwholesome volitional impulses, and, unwholesome, voluntary impulses to act, while, virāga counteracts ego involvement, fixation on outcomes, and, assists, with ethical consistency under pressure. These sets are viewed as operating situationally as system. Re-establishing both the ethical and epistemic coherence of Buddhist self-management, this study provides a conceptually sound alternative to the more instrumental and reductionist interpretations of mindfulness and emotional regulation. In leadership and organizational studies, it advances an integrated model of ethical self-regulation that considers the interplay of the three components of Buddhism, i.e., morality, emotional regulation, and wisdom, without collapsing Buddhist doctrine to instrumentalist ends.